She had been healthy a when he married her - Emmanuelle Roussel (Anglophonia)
This paper presents the main points of a contrastive study of English and French based on the way the two time systems work. First the behaviour of the English past perfect -when transposed into French -is examined, and the author gives the real reason why it can correspond to three different forms in French (namely the plus-que-parfait, the passé antérieur and the imparfait). Then the author explains why some statements in the past perfect will be translated into an imparfait (only). Finally the interest lies in the way comment is expressed in each language. Actually the past perfect cannot be used to comment on something, whereas the imparfait can. The author shows here how the phenomenon works and what its consequences are concerning translation. She also puts forward a new definition of the way the whole time system of English is organised. Mainly in terms of preconstruction.